A jugoszláv lakosok külföldre távozásának szociológiai vetülete (Szociológiai Szemle, 2024)
The emigration of Yugoslav population has been going on for three decades. Its first wave when people were taking up temporary jobs in the developed capitalist countries started after 1965, when the socio-economic reform was started after World War II. The state wished to solve the problem of agricultural overpopulation, unemployment and unskilled labour by opening the borders. By the early eighties it was the migration of trained labour and experts which became characteristic. The goal of migration was the countries of Western and Northern Europe (the FRG, Austria and France). By the late eighties it was economic migration. Now, in the nineties the motivations of migration change: it has political as well as psychological causes, the danger of war and military mobilisation, forced removals of people from their homes give a new dimension to the emigration of Yugoslavs. They go away in masses, young experts and entire families leave. In my paper I have pointed out the characteristics and dimensions of economic emigration, its motivations, the extent of adjustment to the new environment.